2020
DOI: 10.3390/ijms21082961
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Inhibits PEDV Infection and Proinflammatory Cytokine Secretion via the HMGB1/TLR4-MAPK p38 Pathway

Abstract: Our previous study showed that glycyrrhizin (GLY) inhibited porcine epidemic diarrhea virus (PEDV) infection, but the mechanisms of GLY anti-PEDV action remain unclear. In this study, we focused on the anti-PEDV and anti-proinflammatory cytokine secretion mechanisms of GLY. We found that PEDV infection had no effect on toll-like receptor 4 (TLR4) protein and mRNA levels, but that TLR4 regulated PEDV infection and the mRNA levels of proinflammatory cytokines. In addition, we demonstrated that TLR4 regulated p38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 54 publications
(80 reference statements)
1
31
0
Order By: Relevance
“…The PEDV N antibody used herein was generated in our laboratory. The anti-PEDV-N polyclonal antibody was prepared in rabbits using PEDV-N protein as antigen and western blot and IFA were diluted 1:5,000 and 1:500, respectively ( Gao, et al, 2020 ). The β-actin antibody was purchased from TransGenBiotech (China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PEDV N antibody used herein was generated in our laboratory. The anti-PEDV-N polyclonal antibody was prepared in rabbits using PEDV-N protein as antigen and western blot and IFA were diluted 1:5,000 and 1:500, respectively ( Gao, et al, 2020 ). The β-actin antibody was purchased from TransGenBiotech (China).…”
Section: Methodsmentioning
confidence: 99%
“…The western blotting procedure followed previous descriptions ( Huan, et al, 2017 ; Gao, et al, 2020 ). PEDV N and actin were detected using the above-mentioned primary antibody and a secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gycyrrhizin. Unknown Pompei et al, 1979 Pompei et al, 1980 Sato et al, 1996 Cinatl J et al, 2003 Hoever et al, 2005 Wolkerstorfer et al, 2009 Michaelis et al, 2011 Dao et al, 2010 Ashfaq et al, 2011 Hardy et al, 2012 Matsumoto et al, 2013 Yu et al, 2014 Laconi et al, 2014 Duan et al, 2015 Baltina et al, 2015 Chen Q et al, 2017 Si et al, 2018 Liang et al, 2019 Baltina et al, 2019 Gao et al, 2020 Tong et al, 2020 Chen and Du, 2020 …”
Section: Antiviral Effect Of Glycyrrhizin and Licorice Extractmentioning
confidence: 99%
“…Studies further revealed that the inactivation of NF- κ B led to a reduced expression of different proinflammatory cytokines like IL-1 β , IL-6, TNF- α , and HMGB1 ( Figure 2 ) [ 129 , 139 , 140 ]. GL was capable of blocking porcine epidemic diarrhea virus infection, as well as reduced proinflammatory cytokine expression via the HMGB1/TLR4-p38MAPK pathway ( Figure 2 and Table 1 ) [ 141 ].…”
Section: Toll-like Receptorsmentioning
confidence: 99%